Health Impact of Household Waste Burning in Khartoum State, Sudan - Waleed Makki H; Waleed Makki H; Mohamed TSA; Omer Hamad Abd El‑Raheem G; Bashir Abdel Mahmoud AZ; Mustafa Elfadul M; Homeida M; Noma M (Dove Medical Press, 2023)
Hiba Waleed Makki,1 Hana Waleed Makki,1 Tala Siefuddin Awadelkarim Mohamed,2 Ghada Omer Hamad Abd El‑Raheem,3 Al-Zamzami Bashir Abdel Mahmoud,4 Maisa Mustafa Elfadul,5 Mamoun Homeida,6 Mounkaila Noma2 1Faculty of Medicine, University of Medical Sciences and Technology, Khartoum, Sudan; 2Postgraduate Diploma Research Methodology & Biostatistics, Graduate College, University of Medical Sciences and Technology, Khartoum, Sudan; 3Soba University Hospital & Research Methodology and Biostatistics, Faculty of Medicine, University of Medical Sciences and Technology, Khartoum, Sudan; 4Faculty of Disaster and Humanitarian Security, International University of Africa, Khartoum, Sudan; 5Public Health, Graduate College, University of Medical Sciences and Technology, Khartoum, Sudan; 6University of Medical Sciences and Technology, Khartoum, SudanCorrespondence: Hiba Waleed Makki, Tel +249 906566001, Email hibawaleed70@gmail.comBackground: Waste disposal and management is a global concern affecting both high- and low-income countries. This research assessed the health impact of burning household waste in Khartoum State, Sudan.Methods: An online community-based cross-sectional study was implemented on a sample of 844 participants selected through a stratified random sampling technique across Khartoum State. The data were collected through a standardized pre tested online questionnaire. The data file was georeferenced through Google Earth Pro and analysed with SPSS 23 and ArcGIS 10.3. The data were summarized numerically and graphically. The appropriate frequency tables were used in ArcGIS to generate geographical distribution maps of household waste burning and predictive health risk maps of waste burning in Khartoum State. Statistical tests performed for association carried out were Chi-square and ANOVA. A binary regression analysis established the relationship between burning of household waste and its associated factors. All statistical tests were considered significant when p < 0.05.Results: The practice of burning household waste was performed by 74.5% (619/831) of the participants with 50.8% (311/612) who reported burning the waste weekly. The health conditions related to household waste burning were predominately asthma (57.0%) and respiratory manifestations (38.0%). Of the ten contributing factors of health risks related to burning household waste, the two statistically significant were the frequency of waste collection (OR = 0.720, 95% [CI: 0.593- 0.875], p = 0.001) and the place of waste disposal (OR = 0.791, 95% [CI: 0.651- 0.961], p = 0.018).Conclusion: The practice of burning household waste in Khartoum State was a public health concern. Sociodemographic and managerial factors exposing residents to health risks appeal political, health authorities and communities to establish a partnership to manage household waste for public safety and good quality of life.Keywords: burning waste, health risk, household waste, municipality waste collectors, open discharge, waste collection